Differentiation of biosolids from animal faecal material using the 16s ribosomal RNA genetic markers of gastrointestinal anaerobic bacteria - Ho, K.; Pritchard, Deborah; Penney, N. (International Water Association, 2007)
Recombinant DNA techniques were evaluated for their usefulness in distinguishing biosolids from faecal material of cow, kangaroo and sheep. It involved PCR amplification using published priming sequences, and restriction site profiling of amplified DNA across the 16S rRNA gene of anaerobic gastrointestinal bacteria, Bacteroides spp and Bifidobacteria spp. Of the three Bacteroides spp primer pairs, two were useful for cow faecal material though at lower annealing temperatures were also applicable to biosolids and sheep faecal material. The third primer pair was specific only for biosolids. All three primer pairs were not able to PCR-amplify Bacteroides spp sequences in faecal material of kangaroo. Of the three Bifidobacteria spp primer pairs, one was useful for sheep faecal material though at lower annealing temperature was also applicable to biosolids and cow and kangaroo faecal material. The Bifidobacterium angulatum specific primer pair enabled the PCR detection of anaerobes only in biosolids and in faecal material of kangaroo. The third, a Bifidobacterium catenulatum specific primer pair was suitable for faecal material of cow and at lower annealing temperatures was also applicable to the sample from sheep. For some primer sets, PCR amplification alone could not differentiate biosolids from other faecal samples. However, this could be resolved by digesting amplified DNA with the appropriate restriction enzymes. Overall, our evaluations show that recombinant DNA techniques have the potential to distinguish biosolids from other sources of faecal material, including that from kangaroo.